2003
DOI: 10.1021/om030230x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Steric Effects on the Reductive Elimination of Diaryl Ethers from Palladium(II)

Abstract: Arylpalladium aryloxide complexes containing sterically and electronically varied phosphine ligands were prepared, and the rates for reductive elimination of diaryl ethers from these complexes were studied to determine the ligand properties that most strongly accelerate this unusual reaction. Electronic and steric effects were probed by preparing monomeric palladium complexes of the type (L)Pd(Ar)(OAr‘), in which L = DPPF (1,1‘-bis-diphenylphosphinoferrocene), CF3-DPPF (1,1‘-bis[di(4-(trifluoromethyl)phenyl)ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 95 publications
4
115
0
2
Order By: Relevance
“…Even though a number of metals have been used to mediate this process, the versatility of palladium compounds has remained unsurpassed. [7] The advantages of using NHCs as ligands in Pd mediated reactions are: 1) the strong s-donating ability of NHCs results in a Pd center capable of oxidative addition into bonds traditionally considered resistant, for example, in chloroarenes [132] or alkyl halides; [133,134] 2) the steric bulk of NHCs facilitates reductive elimination in a manner analogous to bulky phosphanes; [135,136] and 3) the strong Pd-NHC bond and limited decomposition pathways available ensure that the metal is kept in a soluble, catalytically active state even when only a single NHC is attached. As a consequence of the special complexation properties of NHCs to Pd, well-defined complexes that are stable, easy to synthesize, yet readily activated under the reaction conditions offer definite advantages over catalysts formed in situ.…”
Section: Applications Of Pd-nhc Catalysts In Crosscoupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though a number of metals have been used to mediate this process, the versatility of palladium compounds has remained unsurpassed. [7] The advantages of using NHCs as ligands in Pd mediated reactions are: 1) the strong s-donating ability of NHCs results in a Pd center capable of oxidative addition into bonds traditionally considered resistant, for example, in chloroarenes [132] or alkyl halides; [133,134] 2) the steric bulk of NHCs facilitates reductive elimination in a manner analogous to bulky phosphanes; [135,136] and 3) the strong Pd-NHC bond and limited decomposition pathways available ensure that the metal is kept in a soluble, catalytically active state even when only a single NHC is attached. As a consequence of the special complexation properties of NHCs to Pd, well-defined complexes that are stable, easy to synthesize, yet readily activated under the reaction conditions offer definite advantages over catalysts formed in situ.…”
Section: Applications Of Pd-nhc Catalysts In Crosscoupling Reactionsmentioning
confidence: 99%
“…As the oxidative addition intermediate is some 25 ) than the oxidative addition (29 kJ mol À1 ). [136] authors concluded that chloromethane would not undergo oxidative addition in the gas phase. However, cross-coupling reactions of alkyl halides, including chlorides, [147] are facile with Pd-NHC catalysts in polar solvents (Scheme 54).…”
Section: The Catalytic Cycle Of the Pd-nhc-mediated Cross-coupling Rementioning
confidence: 99%
“…The rate of reductive elimination is relatively fast with the sterically encumbered ligand L3, thus precluding efficient conversion of 64 into 67 and leading to the reaction following path a. The rate of reductive elimination with L1 is slower, [44] thereby allowing enough time for conversion into the more stable species 67 and ultimately to the reaction following path b. Thus, the reason for the difference in the findings made by the research groups of Beletskaya and Rouden may lie in the ability of rigid cyclic diamines to efficiently interconvert between 64 and 67.…”
Section: Chemoselective Transformations Of Oligoaminesmentioning
confidence: 99%
“…Methode A: 1 oder Chloralkanen; [133,134] 2) wegen des Platzbedarfs der NHCs ist ebenso wie bei sperrigen Phosphanen die reduktive Eliminierung erleichtert; [135,136] 3) wegen der starken Pd-NHC-Bindung und den wenigen möglichen Zerfallswegen bleibt das Metall, selbst wenn nur ein einziger NHC-Ligand koordiniert ist, sicher in einem löslichen, katalytisch aktiven Zustand. Durch die besonderen Komplexierungseigenschaften von NHCs an Pd sind also definierte Komplexe synthetisierbar, die leicht aktiviert werden können und gegenüber in situ hergestellten Komplexen viele Vorteile bieten.…”
Section: Anwendung Von Pd-nhc-katalysatoren In Kreuzkupplungenunclassified